Device for Conductive Coatings Quality Control of Rocket and Space Technique Elements - B. V. Skvortsov; A. S. Samsonov; S. A. Borminskiy; D. M. Zhivonosnovskaya (Приборы и методы измерений)
The widespread use of cryogenic fuels in the aerospace industry necessitates additional thermal insulation of aircraft fuel tanks. At the same time a static charge may occur on the heat insulating layer during operation which can lead to an explosion if fuel leaks. To avoid such situations an antistatic conductive coating is applied to the insulation. The aim of the study is to develop a device for remote control of conductive coatings of aircraft fuel tanks which allows to quick find and mark damaged areas.The developed method consists in changing the electrical capacitance between the conductive coating of the controlled object and the scanning electrode allowing to identify hazardous in terms of sparking closed shape defects. The basic technical requirements for the device were formed and the required minimum size of the monitored defect were indicated. The design features necessary for the implementation of the device were considered. A block diagram were developed on the basis of which an experimental bench for capacitive control were created which were is based on the bridge measurement method.The article presents the results of the finite-difference calculation of the electric field in the structure of a capacitive sensor in the presence of a defect, the dependence of the capacitance of the sensor on its displacement over the defective area was also obtained. As the result of experimental studies the experimental data obtained confirmed the theoretical calculations and the correctness of the mathematical model with an accuracy of no worse than 5 %, the absolute error of fixing the defect ± 2 mm at a scanning speed of 0,02 m/s. Was shown that the total error of fixing the coordinates of the defect at different positions of the air gap sensor, temperature and scanning speed lies in the range of 1,5–6,5 mm. The materials presented in the article make it possible to increase flight safety by reducing the likelihood of sparking.